DETERMINING THE OPTIMAL SOWING DATES FOR OAK SPECIES SEEDS IN FOREST NURSERIES - I. Z. Yangibayeva; B. I. Eshankulov (Modern American Journals, 2025)
The trees of the genus Quercus are known for their high-quality wood, ornamental value, and adaptability to unfavorable climatic factors. In Uzbekistan, representatives of the Quercus genus were absent about two centuries ago. However, at present, the common oak is becoming one of the most widely cultivated species in the major cities of the country. As a result, interest in other species of oak is also growing. Currently, experiments are being conducted on the introduction of different oak species and the cultivation of their saplings.
Keywords: Oak, species, natural, cultural, wood, ornamental, forest, technology, intensive, tree, sapling, standard.